Fish Assemblages Associated With Oil and Gas Platforms in the Gulf of Thailand - Harvey, Euan S.; Watts, Stephanie L.; Saunders, Benjamin J.; Driessen, Damon; Fullwood, Laura A. F.; Bunce, Michael; Songploy, Se; Kettratad, Jes; Sitaworawet, Paweena; Chaiyakul, Sarin; Elsdon, Travis S.; Marnane, Michael J. (Frontiers in Marine Science, 2021)
Decommissioning of offshore oil and gas structures is either occurring, or imminent in most regions of the world. Most jurisdictions require that offshore structures be removed for onshore disposal. However, there is growing interest in understanding the ecological and socio-economic benefits of leaving structures in the water. Descriptions of how fish utilize the vertical structure created by wellhead platform jackets (platforms) will provide insights into possible outcomes of decommissioning alternatives, such as full removal, leave in-situ, or translocation to a designated reefing site. We surveyed fish assemblages associated with seven platforms and five reference sites located ~150 km offshore in the central Gulf of Thailand. The platforms spanned the entire water column (~75 m) and were a mix of three and four legged structures. We used a Remotely Operated Vehicle (ROV) fitted with an underwater stereo video system to quantify the abundance, size, biomass and economic value of fish associated with the platforms. We recorded 43 species of fish on the platforms and five reference sites with most fishes on platforms categorized as coral-reef or coral-reef-associated species. We observed a strong vertical zonation in the fish assemblage on the platforms. The Regal demoiselle (Neopomacentrus cyanomos) was numerically dominant (75% of all fish observed). We measured 3,933 kg of fish on the platforms with Caranx sexfasciatus accounting for 76.12% of that. We conservatively estimate each platform had a scaled mean biomass of ~2,927 kg and the fished species had scaled mean economic value of 175,500 Thai Baht per platform. We estimated that the biomass of fish associated with the seven platforms was at least four times higher per unit area than some of the world’s most productive coral reefs.